Environmental Burden of Disease in the Netherlands. (13th November 2019) - Hilderink, H; Schram, D; Plasmans, M
Abstract: Background: RIVM-National Institute for Public Health and the Environment published as part of the 2018 Dutch Public Health Foresight report, an update of the Disease Burden, including the Environmental Burden of disease. This report is not only relevant for the Ministry of Health but also for other policy arenas, to support policy making with the objective of improving health. Methods: Environment factors are distinguished by indoor and outdoor environment. The following environmental factors have been taken into account; Air pollution (PM10/NO2), UV radiation, noise, second-hand smoking, carbon monoxide poisoning and indoor dampness. The effects of chemical substances are not included. Making use of the population attributable fraction, the fraction part of mortality, disease burden and health care expenditures attributable to environmental factors is calculated. For this method, data on exposure as well as the dose-response relationship (relative risks) are used. Results: Some 4% of the disease burden in the Netherlands is caused by environmental factors and that costs us more than 1 billion euros of care per year. This corresponds with 200, 000 DALYs; of which 175, 000 by outside environment and 25, 000 by indoor environment. In total, almost 13000 deaths can be attributed to environmental factors. Air pollution causes by far most of this disease burden. After that, exposure to UV radiation and second-hand smoking rank highest. Conclusions: A considerable disease burden, number of deaths and health expenditures is attributable to environmental factors and could at least in theory be avoided by improving our environment. Air pollution in particular plays an important role in this. In addition, even a greater health gain could be achieved if environment factors are tackled and healthy behavior is at the same time stimulated.